2020
DOI: 10.1038/s41598-020-64552-w
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of patient-derived xenografts from patients with gastrointestinal stromal tumors: analysis of clinicopathological characteristics related to engraftment success

Abstract: patient-derived xenografts (pDXs) can represent the heterogeneity and histological characteristics of tumors and are thus useful for testing the efficacy of anti-cancer drugs; however, PDXs are difficult to generate, especially for gastrointestinal stromal tumor (GIST). We analyzed the clinicopathologic factors associated with the successful establishment of GIST PDX in NOD.Cg-Prkdc scid IL2rg tm1Wjl /SzJ mice. We used 185 GIST tumor fragments from patients who underwent surgical resection prior to (n = 66; 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…One possibility for the higher engraftment rate is that when tumor tissue samples are implanted into immunodeficient mice, cells with strongly positive Ki-67 own high proliferation capacity. Similar results were also reported in PDX models of other types of cancer (31)(32)(33)(34). Besides, our results showed that a higher engraftment rate was observed in dMMR tumors, while no significant association was observed between other important gene mutations (e.g., KRAS and BRAF mutations) and engraftment rate.…”
Section: Discussionsupporting
confidence: 91%
“…One possibility for the higher engraftment rate is that when tumor tissue samples are implanted into immunodeficient mice, cells with strongly positive Ki-67 own high proliferation capacity. Similar results were also reported in PDX models of other types of cancer (31)(32)(33)(34). Besides, our results showed that a higher engraftment rate was observed in dMMR tumors, while no significant association was observed between other important gene mutations (e.g., KRAS and BRAF mutations) and engraftment rate.…”
Section: Discussionsupporting
confidence: 91%
“…Modeling TKI-resistant SDH-deficient GIST is needed to find effective therapies for this patient population. Existing GIST models are primarily for KIT-mutant GISTs, while SDH-deficient GISTs have been difficult to model (6)(7)(8)(9). Models for SDH-deficient tumors are limited and the downstream effects of SDH-loss and succinate accumulation is primarily studied by knockdown or genetic depletion of SDH subunits in already established cell lines, murine or hamster cells (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%